Impact of drying temperature on tissue anatomy and cellular ultrastructure of different aromatic plant leaves. (4th July 2022) - Vallino, Marta; Faccio, Antonella; Zeppa, Giuseppe; Dolci, Paola; Cerutti, Elena; Zaquini, Lucia; Faoro, Franco; Balestrini, Raffaella
Abstract: Herbs are processed by drying to decrease the moisture content and therefore to inhibit the growth of microorganisms, reducing the alterations during the storage and creating shelf-stable products. The drying of aromatic herbs has been carried out over the years as convective drying with hot air but information on the impact of this process at cellular level is still limited. In this work, conventional hot-air drying technique was compared to a cold drying method emerging in recent years to evaluate the cellular damages in four economically important aromatic herbs such as lemon balm, mint, mallow and savory. Results suggest that the two applied drying technologies differently affect the cellular structure in the diverse species, representing a basis for future researches in the optimization of the whole process and in decision making.